2019
DOI: 10.1051/e3sconf/20199801025
|View full text |Cite
|
Sign up to set email alerts
|

The geochemistry of water and gas phases from high pCO2 sparkling springs within the northern Sikhote-Alin ridge region (Russian Far East)

Abstract: Two types of cold CO2 rich groundwaters are located within the northern part of the Sikhote-Alin ridge: the first type is a Ca–Mg–HCO3 water with low TDS content (≤ 1.7 g/l) and high concentrations of Fe2+, Mn2+, Ba2+, and SiO2, whilst the second type is a Na–HCO3 water with a high TDS content (≈ 14 g/l) and elevated concentrations of Li+, Btot, Sr2+, Br–, and I–. A notable feature of these waters is a predominance of CO2 in the gas phase (up to 99 vol. %) and low contents of other gases (CH4, N2, O2, etc.). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In Fig. 5, the He isotopic compositions are shown for both aquifers in the Mukhen springs (Kharitonova et al 2019), compared with the newly obtained data by this study for several springs in the far eastern region (Table 2). The locations of the springs are shown in the inset of Fig.…”
Section: Distinct Isotopic Features Of Two Groundwaters In Mukhen Spamentioning
confidence: 84%
See 1 more Smart Citation
“…In Fig. 5, the He isotopic compositions are shown for both aquifers in the Mukhen springs (Kharitonova et al 2019), compared with the newly obtained data by this study for several springs in the far eastern region (Table 2). The locations of the springs are shown in the inset of Fig.…”
Section: Distinct Isotopic Features Of Two Groundwaters In Mukhen Spamentioning
confidence: 84%
“…With respect to the genesis of high-pCO 2 water, several mechanisms associated with young volcanism have been suggested, and several studies have shown that most high-pCO 2 waters have a meteoric origin (Kharitonova et al 2017). Recently, Kharitonova et al (2019) observed a high 3 He/ 4 He ratio in the Mukhen springs, indicating that these springs originated from a considerable depth. The He isotopic system is a strong indicator to distinguish the contributions from various sources, particularly those from crustal and mantle rocks.…”
Section: Introductionmentioning
confidence: 99%